جدیدفقہی مسائل میں قراءاتِ قرآنیہ سےاستدلال کا منہج - Madni, Qari Abdul Nasir; Hafiz Masood Qasim; Zahid Husain Shakri (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2022)
It is an indisputable fact that Allah Almighty has revealed the Holy Qur’an in different dialects that beholds wisdom. It is upon Muslim scholars to convey the Qur’an to its readers and to translate and interpret underlying wisdom in it. In fact, the Holy Qur’an is the valid source that provides the fundamental principles of Islamic Jurisprudence. This is the reason why the Jurists have keenly explored the Holy Qur’an in every age. They had made arrangements to learn the knowledge of recitations and refer to the readers in time of need so that the recitations could indicate the effects of modern Jurisprudence. In this Article, an attempt has been made to bring forth the examples from the recitations of the Holy Qur’an which have an effect on the rules of Jurisprudence which are directly related to modern Jurisprudential issues:1) the Maqam-e-Ibrahim is commanded to offer prayers; 2) What is the ruling on fighting within the limits of Haram Shareef ? 3) What is the ruling of Islamic excuse for a wife? 4) What is the order of ablution in case of holding the wife by hand? 5)Torture is prohibited for secretary and witness.6) What is the true ruling on entering Islam? And at the end of the article, the summary is briefly stated. Key Words: Method of reasoning,Qur’anic recitations,Modern jurisprudence issues.